Evaluating the Role of Genetic Markers in Predicting Oral Leukoplakia Malignancy Transformation - Ahtesham Ahmad Qurishi; Mohamed S. Mohamed Morsy; Abeer M. Atout; Shahad Essa Abzoah; Mohammed Hasan M. Wadani; Nawaf Hussain Ali Ghazwani; Shatha Ahmad Mohammad Jafari (Journal of Pharmacy and Bioallied Sciences)
Background: Oral leukoplakia is a common premalignant lesion in the oral cavity, with varying risks of transformation into oral squamous cell carcinoma (OSCC). Identifying reliable genetic markers to predict malignant transformation is crucial for early intervention and improved patient outcomes. Materials and Methods: A prospective cohort study was conducted on 150 patients diagnosed with oral leukoplakia. Tissue samples were collected from all patients and analyzed for genetic markers, including p53, cyclin D1, and microsatellite instability. Patients were followed up for a period of 24 months to monitor any transformation to OSCC. Genetic expression was quantified using real-time PCR, and histopathological confirmation of malignancy was performed. Results: Out of 150 patients, 30 (20%) showed positive expression of p53, 45 (30%) exhibited overexpression of cyclin D1, and 25 (16.7%) displayed microsatellite instability. Among the patients with genetic marker expression, 18 (60%) of the p53-positive cases and 22 (48.9%) of the cyclin D1-positive cases developed OSCC. Additionally, 10 (40%) of those with microsatellite instability experienced malignant transformation. The combined presence of p53 and cyclin D1 overexpression was significantly associated with a higher risk of transformation (P < 0.05). Conclusion: This study highlights the potential role of genetic markers, such as p53, cyclin D1, and microsatellite instability, in predicting the malignant transformation of oral leukoplakia. The findings suggest that the combination of these markers may serve as a valuable tool for early diagnosis and risk stratification in patients with oral leukoplakia.